The role of age and maturation on jump performance and postural control in female adolescent volleyball players over a season - Bertozzi, F.; Brunetti, C.; Maver, P.; Galli, M.; Tarabini, M. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background Jump performance and postural control are essential for success in technical/tactical actions and overall playing performance in volleyball. Youth athletes undergo significant physical and neuromuscular development during adolescence, which can impact these abilities. This study examined the effect of age and biological maturity, assessed as the distance from peak height velocity using the maturity offset (MO), on vertical and plyometric jumping abilities and postural control in adolescent female volleyball players across different age categories throughout a competitive season.